'Because my brain isn't as active as it should be, my eyes don't always see': a qualitative exploration of the stress process for those living with posterior cortical atrophy. Issue 2 (8th February 2018) - Harding, Emma; Sullivan, Mary Pat; Woodbridge, Rachel; Yong, Keir X X; McIntyre, Anne; Gilhooly, Mary L; Gilhooly, Kenneth J; Crutch, Sebastian J
Abstract : Objectives: To explore the stress process for individuals living with posterior cortical atrophy (PCA) and their families. Design: A qualitative study using in-depth semi-structured dyadic and individual interviews with people living with a diagnosis of PCA and a family carer. Interview transcripts were thematically analysed. Setting: Participants' homes. Participants: 20 individuals in the mild to moderate stages of PCA and 20 family carers. Findings: Three major themes were identified: (1) the diagnostic journey: mostly an unsettling and convoluted process, owing to the early age of onset, rarity and atypical symptom profile of PCA. (2) Interactions with the physical environment: profound difficulties with functional and leisure activities were usually compensated for with adaptations maximising familiarity or simplicity. (3) Implications within the psychosocial environment: symptoms impacted individuals' sense of independence and identity and required reallocations of roles and responsibilities. Ongoing uncertainties and the progressive nature of PCA caused most dyads to take a 'one day at a time' approach to coping. Relatively well-preserved insight and memory were a benefit and burden, as individuals shared the illness experience with family members and also compared their current situation to pre-diagnosis. The experience was framed by background and contextual factors and understood within an ever-changing temporal context. Conclusion: The stress process in PCA is characterised by uncertainty and unpredictability from diagnosis through to ongoing management. The provision of tailored information about cortical visual problems and associated functional difficulties, time-sensitive environmental adaptations to help those with PCA to identify what and where things are and psychosocial interventions for the marital/family unit as a whole would be useful to improve both functional status and psychological well-being. Future research exploring (1) stress and coping in the later stages of PCA and (2) the nature and impact of visual impairment(s) in typical Alzheimer's disease would be worthwhile.